Verifikasi Model Matematis dan Persamaan Empiris Perilaku Pestisida Organofosfor di Tanah Sawah Hasil Pengamatan Laboratorium pada Tanah Sawah Sebenarnya - Rahayuningsih, Edia (Fakultas Teknik , UGM, 2008)
The mathematical model was selected and the empirical equations were formulated from laboratory measurement by disturbed soil that was applied in undisturbed soil or field soil required a correction factor. The correction factor could be expressed as a value of channeling fraction. The channeling process will affect to the average velocity of soil solution flow in soil. The average velocity of soil solution flows in soil controlled the fate of pesticide in undisturbed soil. The soil solution flows at undisturbed soil were expressed as two difference velocity values. The first part has equal velocity as its superficial velocity. The second part, because of channeling, it was arbitrarily determined to be 10 times of the superficial velocity, and therefore, the superficial velocity of soil solution in the undisturbed soil must be corrected by the channeling fraction. The objective of the verification experiment was to identify a correction factor that could be expressed as channeling fraction in the equation as follows: